Mota-Engil new prospects of growth: overcoming the financial crisis - Melim, Nuno Guilherme Dantas (2015)
The 2008 global financial crisis caused the collapse of business key sectors, declines in consumer wealth and a fall in economic activity resulting in a global recession. In some European countries, the 2008 crisis contributed to a sovereign-debt crisis which had a strong impact in Southern European countries. The construction sector was particularly affected, with budget cuts disturbing public investment and no financing available for private constructors. This report intends to explain how Mota-Engil, faced this situation of low growth, and which strategies were adopted by the management to overcome the difficult economic conjecture, mainly in its domestic market: Portugal. The report is organized as a case-study. The first part, the case narrative, is subdivided into 6 parts, and the second part is the teaching note. The teaching note is constituted by the four questions and their respective responses.